2007
DOI: 10.1021/ma070288d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled High-Speed Anionic Polymerization of Propylene Oxide Initiated by Onium Salts in the Presence of Triisobutylaluminum

Abstract: The conventional anionic polymerization of propylene oxide (POx) proceeds at a very slow rate in low polar media and is characterized by an important transfer reaction to monomer. This only allows the formation of poly(propylene oxide) oligomers. A new polymerization strategy allowing the fast and controlled anionic polymerization of POx has been developed. It is based on the formation of complexes with both the anionic initiator and the monomer. The influences of alkali metal alkoxides (i-PrONa), ammonium sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(157 citation statements)
references
References 12 publications
(17 reference statements)
8
136
0
5
Order By: Relevance
“…Polymerization of Ethoxyethyl Glycidyl ether and t-butyl Glycidyl Ether A binary initiating system constituted of NOct 4 Br as initiator and i-Bu 3 Al as catalyst/activator has been recently reported by us for the controlled anionic polymerization of epoxides [30][31][32][33] in hydrocarbon media. This system was investigated for the polymerization of EEGE and t-BuGE, as a protected form of glycidol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymerization of Ethoxyethyl Glycidyl ether and t-butyl Glycidyl Ether A binary initiating system constituted of NOct 4 Br as initiator and i-Bu 3 Al as catalyst/activator has been recently reported by us for the controlled anionic polymerization of epoxides [30][31][32][33] in hydrocarbon media. This system was investigated for the polymerization of EEGE and t-BuGE, as a protected form of glycidol.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests an apparent zero monomer order for the propagation reaction as already proposed for the monomer-activated mechanism of propylene oxide. [30] Compared to EEGE, polymerization of tBuGE proceeds more readily and goes to completion in a few hours using only 2 equivalents of triisobutylaluminum with respect to the tetraoctylammonium bromide initiator. This can be explained by the presence of a single oxygen atom on the tBuGE and on PtBuGE units, without counting the oxygen atom of the reactive and reacted epoxide function, which is moreover greatly hindered by its tert-butyl substituent.…”
Section: The ([M] 0 -[M]/[m] 0 ) ¼ F(t) Plot Follows a Linear Rate Lamentioning
confidence: 99%
See 2 more Smart Citations
“…In recent works we have found that very simple initiators based on the association of alkali metal derivatives [4,5] or tetralkylammonium or tetraalkylphosphonium salts [6] with triisobutylaluminum (i-Bu 3 Al) yield a rapid and controlled polymerization of propylene oxide whereas transfer to monomer was strongly reduced or even suppressed. As it may be seen in Table 1 In contrast, in the presence of an excess of the aluminic compound, polymerization proceeds rapidly, up to complete monomer conversion.…”
Section: Propylene Oxide Activated Anionic Polymerizationmentioning
confidence: 99%